(untitled) (Development Service Industry Management, 2024)
Gastronomic tourism is becoming increasingly popular due to the growing interest in healthy eating, authentic products and experiences that go beyond the boundaries of ordinary travel. In the modern world, tourists seek not just relaxation, but also a deep immersion in culture through local cuisine. Such trips stimulate the development of the local economy, support farmers, producers and small businesses, and also contribute to the preservation of culinary traditions, which is very important for the post-war recovery of Ukraine. Gastrotourism in Ukraine has the potential to become one of the distinctive features of the country’s tourist attractiveness. However, given the current realities caused by the war, this industry has undergone significant changes, and its future development is in a zone of uncertainty. Despite the large-scale losses suffered by tourist facilities, markets, as well as the general social and psychological situation of citizens, gastrotourism in Ukraine still has prospects for further development. After the war, this type of tourism, in particular for HoReCa, can become a powerful tool for the economic, cultural and social recovery of the country. However, to realize this potential, it is necessary to develop interesting gastronomic tours, hold festivals, fairs, and restore the popularity of authentic cuisine. Gastronomic tourism is a promising direction for the hospitality industry in the modern world. This direction of tourism helps to familiarize tourists with such a part of local culture as national cuisine, which is especially relevant for the post-war reconstruction of Ukraine. Gastronomic tourism attracts people because it allows not only to see new places, but also to learn about culture through taste sensations. National dishes, local products and culinary traditions reveal the peculiarities of the region, its history and way of life. This is a unique experience that combines travel with the discovery of gastronomic treasures of the world, contributing to a better understanding of different cultures. Taking into account the relevance of this topic, the article examines the essence and peculiarities of gastronomic tourism and innovative approaches to its organization in the conditions of post-war reconstruction of Ukraine.